Necessity of Fire Safety Measure Intervention among Garment Workers - Rimmi, Sumaya Hossin; Jahid, Md Istiak; Hossain, Showlin; Chowdhury, Muhammad Muniruzzaman; Mostarin, Somaya; Abbas, Md Golam (Mediscope, 2023)
Background: Providing Bangladesh with low-cost garment industries has had terrible results, including fires and building collapses that have claimed lives and injured hundreds of employees. Objective: This study was carried out to assess the effectiveness of educational intervention programs in increasing fire safety measures among garment workers. Methods: This was a quasi-experimental study conducted among purposively selected 160 garment workers with a semi-structured questionnaire through face-to-face interviews from 1st January to 31st December, 2021 in a factory situated in Narayanganj district. Results: Before the educational intervention, about one-third (29.4%) of respondents had a strong awareness of fire safety; after the intervention, that number increased to 92.5%. All of them (100.0%) had clear knowledge about fire alarms and fire extinguishers after the intervention. After the intervention, the percentage of people who needed sufficient training for fire safety measures improved from 70.6% to 95.6%. Conclusion: The results show that there is a critical need for safety intervention in the sector, which may include safety training for industry workers and health education to reduce the number of fatalities, disabilities, and societal financial burdens. Mediscope 2023;10(2): 50-55